Solving close-coupling equations in momentum space without singularities II - Bray, A.; Abdurakhmanov, I.; Kadyrov, Alisher; Fursa, D.; Bray, I. (Elsevier BV, 2016)
The implementation of the convergent close-coupling method, whereby the principal-value singularity is treated analytically (Bray et al., 2015), has been extended to non-zero angular momenta. Its utility is demonstrated through application to proton scattering on excited states of positronium at incident energies spanning six orders of magnitude. It is shown that the analytic treatment is necessary in the case of highly excited positronium states.